High-temperature-resistant thermal insulation nanosheet and preparation method thereof
Patent Information
- Application Number
- CN202611308286.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-11-03
AI Technical Summary
When existing lightweight thermal insulation materials are used for long-term high-temperature applications, the high surface activity of nanoparticles leads to interparticle sintering, decreased porosity, and a sharp increase in thermal conductivity, resulting in a significant degradation of thermal insulation performance. Furthermore, the preparation process is complex, costly, and has low mechanical strength.
High-temperature resistant heat-insulating nanoplates were prepared by using fumed nano-SiO2 powder as the matrix, combined with components such as silicon micro powder, metakaolin and high-silica glass fiber, through stirring, pressing and sintering processes. Infrared blocking agents were added to inhibit infrared heat penetration.
It maintains excellent thermal insulation properties at high temperatures, resists sintering shrinkage stress, improves mechanical properties, reduces heat transfer, and is suitable for high-temperature environments.
Smart Images

Figure CN123026436A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of refractory materials, specifically to a high-temperature resistant heat-insulating nanoplate and its preparation method. Background Technology
[0002] Lightweight insulation materials are key to achieving energy conservation, emission reduction, and safe operation in high-temperature kilns. Constructing an insulation layer composed of lightweight materials within the kiln lining effectively prevents heat loss through conduction. Replacing heavy refractory bricks with this lightweight insulation material not only significantly reduces heat loss from the furnace body and accelerates heating and cooling rates, but also allows for thinner furnace walls and optimized kiln structure, resulting in significant overall energy savings. Some new materials can even achieve energy savings of over 50%.
[0003] As is well known in the industry, the core heat transfer suppression mechanism of constructing micro- and nano-scale porous structures within materials lies in the fact that when the pore size is smaller than the mean free path of gas molecules, collisions between the pore walls and gas molecules become dominant, thereby effectively suppressing gas-phase heat conduction and convective heat transfer. This "nano-confined" effect is particularly significant at high temperatures—as the temperature increases, the movement of gas molecules intensifies, but due to the confinement of the nanopores, their contribution to the increase in thermal conductivity is limited, allowing the overall thermal conductivity of the material to remain relatively stable over a wide temperature range, significantly better than that of conventional porous materials.
[0004] Based on the above principles, current thermal insulation materials are rapidly developing towards microporous and nanoporous structures. A typical example is silica aerogel, which possesses a nanoscale three-dimensional continuous porous network with a porosity as high as 80-99%, exhibiting extremely low thermal conductivity (as low as 0.013 W / (m·K)) and extremely low density. However, this type of material is prepared by the sol-gel method, and the aerogel precursors used are mostly organosilicon sources. The synthesis process is complex, time-consuming, and costly. Furthermore, it has low mechanical strength, high brittleness, is difficult to mold, and has limited long-term temperature resistance, which restricts its large-scale application. In contrast, fumed silica has a low bulk density and forms a large number of mesoporous structures with pore sizes much smaller than the mean free path of air molecules at room temperature. This effectively suppresses heat transfer in the gas phase. Even at a high temperature of 600°C, its thermal conductivity can still be maintained at 0.020~0.030 W / (m·K), and its thermal insulation performance far exceeds that of traditional inorganic thermal insulation materials. It is also a commonly used carrier for nano-insulation nanoplates. However, when it is used for a long time at a high temperature of 800°C, the high surface activity of the nanoparticles will lead to interparticle sintering, decreased porosity, and a sharp increase in thermal conductivity, resulting in a significant degradation of thermal insulation performance. Summary of the Invention
[0005] To address the aforementioned problems in the prior art, this invention provides a high-temperature resistant insulating nanoplate that exhibits good high-temperature thermal stability and maintains excellent thermal insulation performance in high-temperature application environments.
[0006] The first aspect of the present invention provides a high-temperature resistant heat-insulating nanoplate comprising 65-80 wt% fumed nano-SiO2 powder, 5-15 wt% silica powder, 3-15 wt% metakaolin, 3-10 wt% high silica glass fiber, and 1-5 wt% calcium aluminate cement.
[0007] The metakaolin contains 50-56 wt% SiO2 and 40-45% Al2O3.
[0008] The content of silicon dioxide in the gas-phase nano-SiO2 powder is ≥99.8wt%.
[0009] The silica content in the silica micropowder is ≥99.0 wt%, and the particle size is d. 50 The range is 0.5-3.0 μm.
[0010] The high-silica glass fiber contains ≥96wt% silica and has a length of 3-30mm.
[0011] The high-temperature resistant heat-insulating nanoplate also includes 1-10 wt% of a barrier agent.
[0012] The barrier agent is selected from SiC micro powder, Si3N4 micro powder, TiC micro powder, TiO2 micro powder, ZrO2 micro powder, and K2Ti6O. 13 At least one of whiskers.
[0013] A second aspect of the present invention also relates to a method for preparing the above-mentioned high-temperature resistant heat-insulating nanoplate, comprising the following steps: S1. Preparation of raw materials: Weigh out the following materials by weight percentage: fumed nano-SiO2 powder, silica powder, metakaolin, high silica glass fiber, calcium aluminate cement, and optional barrier agent. S2. Preparation of mixed raw materials: Add the raw materials from step S1 to the mixer in sequence, and mix for the first time. After mixing, introduce steam into the mixer and mix again to obtain the required mixed raw materials for later use. S3. Pressing of mixed raw materials: The mixed raw materials prepared in step S2 are pressed into shape to obtain a molded blank; S4. Drying and firing: Dry the molded blank after pressing in step S3, then heat it to 750~820℃ and keep it at that temperature for 1~3 hours.
[0014] In step S3, the drying temperature is 90~150℃; preferably, the drying temperature is 100~120℃.
[0015] In step S4, the heating rate is 5~20℃ / min; preferably, the heating rate is 5~15℃ / min.
[0016] Compared with the prior art, the high-temperature resistant heat-insulating nanoplate of the present invention has the following beneficial effects: The high-temperature resistant heat-insulating nanoplate of the present invention uses gaseous nano-SiO2 powder as the matrix. By adding an appropriate amount of silicon micro powder and metakaolin, the shrinkage internal stress of the overall heat insulation material can be offset or alleviated, the internal structure can be stabilized and the overall temperature resistance of the material can be improved, and the heat insulation performance under high temperature conditions can be maintained. Attached Figure Description
[0017] Figure 1 This is a SEM image of the high-temperature resistant heat-insulating nanoplate of the present invention. Figure 2 This is a diagram of the internal structure of the high-temperature resistant heat-insulating nanoplate of the present invention. Detailed Implementation
[0018] To make the objectives, technical solutions, and technical effects of the present invention clearer, the technical solutions of the present invention will be further described below in conjunction with the accompanying drawings and embodiments. However, it should be stated that the accompanying drawings and embodiments are not intended to limit the scope of protection of the present invention.
[0019] The high-temperature resistant heat-insulating nanoboard of this invention comprises 65-80 wt% fumed nano-SiO2 powder, 5-15 wt% silica powder, 3-15 wt% metakaolin, 3-10 wt% high-silica glass fiber, and 1-5 wt% calcium aluminate cement. The high-temperature resistant heat-insulating nanoboard of this invention uses fumed nano-SiO2 powder as a matrix, where fumed silica maintains a non-crystalline (amorphous) state well at high temperatures. It has an extremely low thermal conductivity, and the nanoscale primary particle aggregates form numerous mesopores (2-50 nm), with pore sizes much smaller than the mean free path of air molecules at room temperature (~70 nm), effectively suppressing gas-phase heat transfer. Furthermore, its bulk density is extremely low (40-100 kg / m³), significantly reducing the structural load on kilns; it does not react with most media, has strong corrosion resistance, and high chemical inertness, making it suitable for acid and alkaline atmospheres. However, when used for extended periods at 800°C, the high surface activity of the nanoparticles leads to interparticle sintering, decreased porosity, and a sharp increase in thermal conductivity, resulting in a significant degradation of thermal insulation performance. The silicon micropowder added in this invention contains over 99.0% SiO2, ensuring it reacts almost entirely with the matrix or other components at 800°C, acting as a "physical barrier." Furthermore, its high hardness, as a rigid particle, effectively resists the shrinkage stress generated by the sintering of gaseous nano-SiO2 powder, providing stable physical pinning. The silicon micropowder also has an extremely low coefficient of thermal expansion, with a linear expansion coefficient of only about 0.5~1.0×10⁻⁶. -6The temperature is / ℃, far lower than that of the gaseous SiO2 framework. Deformation during thermal cycling is minimal, effectively buffering thermal stress and preventing cracking due to expansion mismatch. Furthermore, its own thermal conductivity is low, having limited impact on overall thermal insulation performance. Adding an appropriate amount of silica powder to a gaseous nano-SiO2 matrix not only optimizes high-temperature mechanical properties but also mitigates the problem of nanoparticle agglomeration. Metakaolin, a dehydroxylated kaolin, is mainly composed of amorphous Al2O3·SiO2 active phase. It undergoes localized chemical bonding with the dangling bonds (≡Si-O·) on the surface of the gaseous nano-matrix SiO2, forming an Al-O-Si bridging structure. Combined with the use of silica powder, this significantly improves tensile strength, resisting sintering shrinkage driven by surface tension at firing temperatures below 820℃ and maintaining thermal insulation performance under high-temperature operating conditions.
[0020] In high-temperature operating environments (especially exceeding 600℃), the contribution of thermal radiation increases dramatically, even becoming the primary pathway for heat transfer. While the nanopores within the gas-phase nano-SiO2 powder matrix can suppress gas heat transfer, they are almost transparent to infrared radiation, allowing heat to directly "penetrate." Therefore, 1-10 wt% of an infrared blocking agent can be added. This infrared blocking agent is selected from SiC micro powder, Si3N4 micro powder, TiC micro powder, TiO2 micro powder, ZrO2 micro powder, and K2Ti6O. 13 At least one of the whiskers. The added infrared blocking agent can "block" the penetration of infrared heat by scattering and absorbing infrared radiation.
[0021] In this invention, the metakaolin contains 50-56 wt% SiO2 and 40-45% Al2O3. The fumed silica nanoparticles contain ≥99.8 wt% silica. The silica microparticles contain ≥99.0 wt% silica. 50 The diameter is 0.5-3.0 μm. The silica content in the high-silica glass fiber is ≥96wt%, and the length of the glass fiber is 3-30mm.
[0022] The high-silica glass fiber added in this invention acts as a skeleton dispersed in the matrix, which can not only disperse and transfer the load, significantly improve the tensile and bending strength, but also enable it to serve for a long time under high temperature conditions of 800°C, avoiding failure that could lead to material collapse and maintaining the overall thermal insulation performance of the material.
[0023] The preparation method of the above-mentioned high-temperature resistant heat-insulating nanoplate of the present invention includes the following steps: S1, preparation of raw materials: weigh fumed nano-SiO2 powder, silica powder, metakaolin, high silica glass fiber, calcium aluminate cement and optional barrier agent according to weight percentage for later use; S2, preparation of mixed raw materials: add the raw materials in step S1 to a mixer in sequence, mix for the first time, and then introduce steam into the mixer and mix again to obtain the required mixed raw materials for later use; S3, pressing of mixed raw materials: press the mixed raw materials prepared in step S2 into a molded blank; S4, drying and firing: dry the molded blank after pressing in step S3, and then heat it to 750~820℃ and keep it at that temperature for 1~3 hours. Figure 1 and Figure 2 SEM images and internal structure diagrams of the high-temperature resistant heat-insulating nanoplates of the present invention are shown respectively.
[0024] In the following embodiments and comparative examples: Vaporized nano-SiO2 powder: SiO2 content ≥ 99.8 wt%, specific surface area 200 m² 2 / g; Silica powder: SiO2 content ≥ 99.0 wt%, d 50 The diameter is 1.5 μm, and the sphericity is ≥90wt%; High silica glass fiber: SiO2 content ≥96wt%, glass fiber length 3-30mm; Metakaolin: SiO2 55.2wt%, Al2O3 42.7wt%, d 50 It is 1.0 μm; Calcium aluminate cement: CA70, particle size <30μm; K2Ti6O 13 Whiskers: length 3–20 μm.
[0025] Example 1
[0026] The high-temperature resistant insulating nanoplate of this embodiment comprises 65 wt% fumed nano-SiO2 powder, 10 wt% silica powder, 10 wt% metakaolin, 10 wt% high-silica glass fiber, and 5 wt% calcium aluminate cement. The preparation method includes the following steps: S1. Preparation of raw materials: Weigh out the fumed nano-SiO2 powder, silica powder, metakaolin, high silica glass fiber and calcium aluminate cement by weight percentage for later use. S2. Preparation of mixed raw materials: Add the raw materials from step S1 to the mixer in sequence, mix for the first time, and then introduce steam into the mixer after mixing for 2 minutes. Mix again for 3 minutes to obtain the required mixed raw materials for later use. S3. Pressing of mixed raw materials: The mixed raw materials prepared in step S2 are pressed into shape at a pressing pressure of 10 MPa to obtain a shaped blank. S4. Drying and firing: The molded blank after pressing in step S3 is dried at 120°C, and then heated to 780°C at a heating rate of 10°C / min, and held at that temperature for 2 hours.
[0027] Example 2
[0028] The high-temperature resistant heat-insulating nanoplate of this embodiment comprises 80wt% fumed nano-SiO2 powder, 5wt% silicon micropowder, 5wt% metakaolin, 5wt% high-silica glass fiber, and 3wt% K2Ti6O. 13 Whiskers and 2 wt% calcium aluminate cement. The preparation method includes the following steps: S1. Raw material preparation: Weigh out the following raw materials by weight percentage: fumed nano-SiO2 powder, silicon micro powder, metakaolin, high-silica glass fiber, and K2Ti6O. 13 Whiskers and calcium aluminate cement are ready for use; S2. Preparation of mixed raw materials: Add the raw materials from step S1 to the mixer in sequence, mix for the first time, and then introduce steam into the mixer after mixing for 2 minutes. Mix again for 3 minutes to obtain the required mixed raw materials for later use. S3. Pressing of mixed raw materials: The mixed raw materials prepared in step S2 are pressed into shape at a pressing pressure of 10 MPa to obtain a shaped blank. S4. Drying and firing: The molded blank after pressing in step S3 is dried at 120°C, and then heated to 780°C at a heating rate of 10°C / min, and held at that temperature for 2 hours.
[0029] Example 3
[0030] The high-temperature resistant heat-insulating nanoplate of this embodiment comprises 75 wt% fumed nano-SiO2 powder, 7 wt% silicon micropowder, 8 wt% metakaolin, 5 wt% high-silica glass fiber, and 3 wt% K2Ti6O. 13 Whiskers and 2 wt% calcium aluminate cement. The preparation method includes the following steps: S1. Raw material preparation: Weigh out the following raw materials by weight percentage: fumed nano-SiO2 powder, silicon micro powder, metakaolin, high-silica glass fiber, and K2Ti6O. 13 Whiskers and calcium aluminate cement are ready for use; S2. Preparation of mixed raw materials: Add the raw materials from step S1 to the mixer in sequence, mix for the first time, and then introduce steam into the mixer after mixing for 2 minutes. Mix again for 3 minutes to obtain the required mixed raw materials for later use. S3. Pressing of mixed raw materials: The mixed raw materials prepared in step S2 are pressed into shape at a pressing pressure of 10 MPa to obtain a shaped blank. S4. Drying and firing: The molded blank after pressing in step S3 is dried at 120°C, and then heated to 780°C at a heating rate of 10°C / min, and held at that temperature for 2 hours. Comparative Example 1
[0031] The high-temperature resistant insulating nanoplate of this comparative example comprises 75 wt% fumed nano-SiO2 powder, 15 wt% silicon micropowder, 5 wt% high-silica glass fiber, and 3 wt% K2Ti6O. 13 Whiskers and 2 wt% calcium aluminate cement. The preparation method includes the following steps: S1. Raw material preparation: Weigh out the following raw materials by weight percentage: fumed nano-SiO2 powder, silicon micro powder, high-silica glass fiber, and K2Ti6O. 13 Whiskers and calcium aluminate cement are ready for use; S2. Preparation of mixed raw materials: Add the raw materials from step S1 to the mixer in sequence, mix for the first time, and then introduce steam into the mixer after mixing for 2 minutes. Mix again for 3 minutes to obtain the required mixed raw materials for later use. S3. Pressing of mixed raw materials: The mixed raw materials prepared in step S2 are pressed into shape at a pressing pressure of 10 MPa to obtain a shaped blank. S4. Drying and firing: The molded blank after pressing in step S3 is dried at 120°C, and then heated to 780°C at a heating rate of 10°C / min, and held at that temperature for 2 hours. Comparative Example 2
[0032] The high-temperature resistant insulating nanoplate of this comparative example comprises 75 wt% fumed nano-SiO2 powder, 15 wt% metakaolin, 5 wt% high-silica glass fiber, and 3 wt% K2Ti6O. 13 Whiskers and 2 wt% calcium aluminate cement. The preparation method includes the following steps: S1. Raw material preparation: Weigh out the following raw materials by weight percentage: fumed nano-SiO2 powder, metakaolin, high-silica glass fiber, and K2Ti6O. 13 Whiskers and calcium aluminate cement are ready for use; S2. Preparation of mixed raw materials: Add the raw materials from step S1 to the mixer in sequence, mix for the first time, and then introduce steam into the mixer after mixing for 2 minutes. Mix again for 3 minutes to obtain the required mixed raw materials for later use. S3. Pressing of mixed raw materials: The mixed raw materials prepared in step S2 are pressed into shape at a pressing pressure of 10 MPa to obtain a shaped blank. S4. Drying and firing: The molded blank after pressing in step S3 is dried at 120°C, and then heated to 780°C at a heating rate of 10°C / min, and held at that temperature for 2 hours.
[0033] The room temperature compressive strength, thermal conductivity at 800°C, linear shrinkage rate, and thermal conductivity at 800°C after service (800°C for 200 hours) of the high-temperature resistant insulating nanoplates of the examples and comparative examples were tested, and the results are shown in Table 1.
[0034] Table 1 The above description is only a preferred embodiment of the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, they can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made without departing from the essential scope of protection claimed by the present invention shall fall within the protection scope of the present invention.
Claims
1. A high-temperature resistant heat-insulating nanoplate, characterized in that: It includes 65-80 wt% fumed nano-SiO2 powder, 5-15 wt% silica powder, 3-15 wt% metakaolin, 3-10 wt% high silica glass fiber, and 1-5 wt% calcium aluminate cement.
2. The high-temperature resistant heat-insulating nanoplate according to claim 1, characterized in that: The metakaolin contains 50-56 wt% SiO2 and 40-45% Al2O3.
3. The high-temperature resistant heat-insulating nanoplate according to claim 1, characterized in that: The content of silicon dioxide in the vapor-phase nano-SiO2 powder is ≥99.8wt%.
4. The high-temperature resistant heat-insulating nanoplate according to claim 1, characterized in that: The silica content in the silicon micropowder is ≥99.0wt%, and the particle size is d. 50 The range is 0.5-3.0 μm.
5. The high-temperature resistant heat-insulating nanoplate according to claim 1, characterized in that: The high-silica glass fiber contains ≥96wt% silica and has a length of 3-30mm.
6. The high-temperature resistant heat-insulating nanoplate according to claim 1, characterized in that: The high-temperature resistant heat-insulating nanoplate also includes 1~10wt% of a barrier agent.
7. The high-temperature resistant heat-insulating nanoplate according to claim 6, characterized in that: The barrier agent is selected from SiC micro powder, Si3N4 micro powder, TiC micro powder, TiO2 micro powder, ZrO2 micro powder, and K2Ti6O. 13 At least one of whiskers.
8. The method for preparing the high-temperature resistant heat-insulating nanoplate according to any one of claims 1 to 7, characterized in that... Includes the following steps: S1. Preparation of raw materials: Weigh out the following materials by weight percentage: fumed nano-SiO2 powder, silica powder, metakaolin, high silica glass fiber, calcium aluminate cement, and optional barrier agent. S2. Preparation of mixed raw materials: Add the raw materials from step S1 to the mixer in sequence, and mix for the first time. After mixing, introduce steam into the mixer and mix again to obtain the required mixed raw materials for later use. S3. Pressing of mixed raw materials: The mixed raw materials prepared in step S2 are pressed into shape to obtain a molded blank; S4. Drying and firing: Dry the molded blank after pressing in step S3, then heat it to 750~820℃ and keep it at that temperature for 1~3 hours.
9. The method for preparing the high-temperature resistant heat-insulating nanoplate according to claim 8, characterized in that: The drying temperature in step S3 is 90~150℃.
10. The method for preparing the high-temperature resistant heat-insulating nanoplate according to claim 8, characterized in that: In step S4, the heating rate is 5~20℃ / min.
